ANALISIS KEBIJAKAN KEUANGAN KAJIAN ARTHASASTRA (RELEVANSI DAN APLIKASI DALAM KONTEKS KONTEMPORER) (Jurnal Manajemen dan Ekonomi (JME), 2024)
This research aims to analyze the financial policies put forward in the Arthasastra, a classic work oneconomics and politics written by Kautilya in the 4th century BC, and explore its relevance andapplication in the contemporary context. Arthasastra provides guidance regarding the management ofstate revenues, tax systems, public expenditures, as well as efficient and responsible financialgovernance. This research uses a qualitative method with a descriptive-analytical approach, where theArthasastra text is studied in depth and compared with modern financial policy practices, especially inthe context of government and fiscal management in Indonesia. The research results show that many ofthe financial principles outlined by Kautilya are still relevant, such as the importance of transparency inpublic financial management, optimizing state revenues through fair taxes, and controlling stateexpenditure. However, there are several differences in context that require adjustments for applicationin a modern financial system that is more complex and globally connected. This research alsoemphasizes the importance of ethics in managing state finances, as outlined by Kautilya, to preventcorruption and improve good governance. Overall, this research concludes that although written in anancient context, the Arthasastra provides valuable insights for modern financial policy, with severalconcepts that can still be adapted to improve the effectiveness of state financial management today.
Keywords: Arthasastra, financial policy, Kautilya, relevance, contemporary application, financial governance.